Facial Animation Based on Feature Points - Beibei Li; Qiang Zhang; Dongsheng Zhou; Xiaopeng Wei (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper presents a hybrid method for synthesizing natural animation of facial expression with data from motion capture. The captured expression was transferred from the space of source performance to that of a 3D target face using an accurate mapping process in order to realize the reuse of motion data. The transferred animation was then applied to synthesize the expression of the target model through a framework of two-stage deformation. A local deformation technique preliminarily considered a set of neighbor feature points for every vertex and their impact on the vertex. Furthermore, the global deformation was exploited to ensure the smoothness of the whole facial mesh. The experimental results show our hybrid mesh deformation strategy was effective, which could animate different target face without complicated manual efforts required by most of facial animation approaches. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2039